THE ANALYSIS OF CSR PRACTICE IN PT. TELKOM (Case Study on CDC PT TELKOM MALANG) - Maria Dias Ika Salama; Noval Adib (Jurnal Ilmiah Mahasiswa FEB, 2014)
This descriptive qualitative study aims to analyze the CSR practices in PT TELKOM, whether it performs in accordance with the principles of CSR. Beside the practice of CSR in PT TELKOM Malang, the problem and solutions occurred in the implementation of CSR in PT TELKOM also are discussed. Case study  is employed as the research design  to answer the research questions. Furthermore, the data collection methods used in this study  are  interview, documentation and observation. The results in this study  reveals  that first, CSR practices in PT TELKOM are performed by supporting unit named Community Development Center (CDC). CDC has two main programs  that are Partnership Program and Community Development Program. Through these two programs CSR practices in PT TELKOM has been implemented    in accordance with the  CSR regulations in Indonesia namely,  Finance  Minister  of Indonesia  Decision No. 1232/KMK.013 /1989 about  Guidelines for Development Low-Income Entrepreneurs and Cooperatives through State-Owned Enterprises,  Act No. 19 of 2003 about  State-Owned Enterprises and Regulation of State-Owned Enterprises Minister Per-05/MBU/2007. Second, the problem occurred in the implementation of CSR in PT TELKOM is bad credit. The solution performed to overcome the existing problem should not be contrast with the CSR  regulation in Indonesia and should prioritize the public interest around the company. There are four steps are applied as the solution  such as  reminding call, reminding letter, direct visit to the business location or domicile of the partners and credit payment rescheduling.Key words:  Corporate Responsibility, Regulation, Indonesia, Implementation of CSR, PT Telekomunikasi Indonesia Tbk.